Tests of Lorentz invariance at the Sudbury Neutrino Observatory - Aharmim, Bassam; Dunford, Monica (Physical review, 2018)
Experimental tests of Lorentz symmetry in systems of all types are critical for ensuring that the basic assumptions of physics are well founded. Data from all phases of the Sudbury Neutrino Observatory, a kiloton-scale heavy water Cherenkov detector, are analyzed for possible violations of Lorentz symmetry in the neutrino sector. Such violations would appear as one of eight possible signal types in the detector: six seasonal variations in the solar electron neutrino survival probability differing in energy and time dependence and two shape changes to the oscillated solar neutrino energy spectrum. No evidence for such signals is observed, and limits on the size of such effects are established in the framework of the standard model extension, including 38 limits on previously unconstrained operators and improved limits on 16 additional operators. This makes limits on all minimal, Dirac-type Lorentz violating operators in the neutrino sector available for the first time.
Gesehen am 26.04.2019